Achievements and new challenges in the area of education of independent Kazakhstan - Zhanar Seysenbayeva., Marat Nuriyev, Damira Sovetkanova, (Opción, 2019)
The article considers the achievements and new tasks in education during years of Kazakhstan’s independence. Education is determined as one of priorities of state policy for social and economic development in the country. Educational programs have to be made with an emphasis on strengthening of practical training of future teachers. It is important to expand the suggestion of elective courses with new courses of practical orientation. One of the major tasks in the solution of the problem on formation of professionalism is a creation of the effective model meeting the modern requirements.